Phylogenetic Inference Using RevBayes. Issue 1 (2nd May 2017) - Höhna, Sebastian; Landis, Michael J.; Heath, Tracy A.
Abstract: Bayesian phylogenetic inference aims to estimate the evolutionary relationships among different lineages (species, populations, gene families, viral strains, etc.) in a model‐based statistical framework that uses the likelihood function for parameter estimates. In recent years, evolutionary models for Bayesian analysis have grown in number and complexity. RevBayes uses a probabilistic‐graphical model framework and an interactive scripting language for model specification to accommodate and exploit model diversity and complexity within a single software package. In this unit we describe how to specify standard phylogenetic models and perform Bayesian phylogenetic analyses in RevBayes . The protocols focus on the basic analysis of inferring a phylogeny from single and multiple loci, describe a hypothesis‐testing approach, and point to advanced topics. Thus, this unit is a starting point to illustrate the power and potential of Bayesian inference under complex phylogenetic models in RevBayes . © 2017 by John Wiley & Sons, Inc.